Calvinist Humor in American Literature - Dunne, Michael, 1941- (Book collections on Project MUSE., 2007)
Though the phrase "Calvinist humor" may seem to be an oxymoron, Michael Dunne, in highly original and unfailingly interesting readings of major American fiction writers, uncovers and traces two recurrent strands of Calvinist humor descending from Puritan times far into the twentieth century. Calvinist doctrine views mankind as fallen, apt to engage in any number of imperfect behaviors. Calvinist humor, Dunne explains, consists in the perception of this imperfection. When we perceive that only others are imperfect, we participate in the form of Calvinist humor preferred by William Bra.